(untitled) (Raparin Journal of Humanities (RJH), 2026)
There are certain circumstances and conditions that both the individual and society pass, wherein they need something that shares the burden with them or alleviates their sorrow and distress. In addition to giving steadiness to the heart, strengthening emotional composure, encouraging determination, and offering empathy and consolation. From this premise our study emerges, titled “Consolation in the Qur’an: A Semantic Study.” It addresses the concept of consolation, as it is one of the significant themes in human experience and has been recognized since early times. Noting that humans as living beings are subject to change by the events unfolding around them as they are evolving. Consolation is a recognized concept in Islam, so long as it remains within the bounds of Islamic law. The Noble Qur’an was revealed by Allah, and the Messengers (peace be upon them) were sent with a comprehensive message that attends to both the external conduct and the internal emotional state. This divine message directs the believer toward fulfillment of their purpose on earth. Numerous verses in the Qur’an articulate meanings related to consolation and support. Upon examining the Qur’anic scholarly interpretations, we find that the interpreters employed a variety of expressions to convey the semantic field of consolation, including terms such as solace, compassion, and condolence. The study is divided into three areas of focus: the first explores the concept of consolation, its meanings, and its lexical equivalents; the second examines the recipients of consolation in the Qur’an; and the third addresses the psychological and spiritual impact of consolatory verses in the context of confronting tribulations. The study includes an introduction, a conclusion, and a comprehensive list of primary and secondary sources.